To solve this system of equations using substitution, we first need to find the value of y in terms of x from the first equation.
y = 2 + 3x
Next, substitute this expression for y into the second equation:
4x - 3(2 + 3x) = -16
4x - 6 - 9x = -16
-5x - 6 = -16
-5x = -10
x = 2
Now that we have found the value of x, we can substitute it back into the first equation to find the value of y:
y = 2 + 3(2)
y = 2 + 6
y = 8
Therefore, the solution to the system of equations is x = 2 and y = 8. This corresponds to choice C: (2, 8).
Solve the system of two equations using substitution.
y=2+3x
4x−3y=−16
A. (−2, 4)
B. (2, 10)
C. (2, 8)
D. (−2, −4)
1 answer